2018
DOI: 10.1182/bloodadvances.2018020222
|View full text |Cite
|
Sign up to set email alerts
|

Clinical consequences of clonal hematopoiesis of indeterminate potential

Abstract: Clonally restricted hematopoiesis is a common aging-associated biological state that predisposes to subsequent development of a hematological malignancy or cardiovascular death. Clonal expansion driven by leukemia-associated somatic mutations, such as DNMT3A, ASXL1, or TET2, is best characterized, but oligoclonality can also emerge without recognized leukemia-driver mutations, perhaps as a result of stochastic neutral drift. Murine models provide compelling evidence that a major mechanism of increased cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
161
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(168 citation statements)
references
References 54 publications
3
161
1
3
Order By: Relevance
“…Positive selection of cells carrying an advantageous somatic mutation will lead to clonal haematopoiesis and skewed XCI patterns as the selected cells will carry the same inactivated parental X. Somatic mutation-driven clonal haematopoiesis is now known to be common in blood of healthy older individuals and is often referred to as clonal haematopoiesis of indeterminate potential (CHIP) 31,48-50 . CHIP is associated with increased risk of both cancer and all-cause mortality 51,52 . The increase in XCI skew in older smokers in our study is consistent with the increase in clonal haematopoiesis observed in smokers 50,53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…Positive selection of cells carrying an advantageous somatic mutation will lead to clonal haematopoiesis and skewed XCI patterns as the selected cells will carry the same inactivated parental X. Somatic mutation-driven clonal haematopoiesis is now known to be common in blood of healthy older individuals and is often referred to as clonal haematopoiesis of indeterminate potential (CHIP) 31,48-50 . CHIP is associated with increased risk of both cancer and all-cause mortality 51,52 . The increase in XCI skew in older smokers in our study is consistent with the increase in clonal haematopoiesis observed in smokers 50,53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…This presents a challenge when seeking to quantify HSC clones from variant data. Applying a flat cutoff to variant data (e.g., VAF > 0.02 defines an HSC clone) is currently the standard for quantifying HSC clones in the clinical and research setting 3,4,31 . Weighted averages derived from ecology and population science such as Shannon entropy 30,32 and the inverse Simpson diversity index 33 can account for all variants in the sample.…”
Section: Selection Of Samples Based On the Fraction Of Informative Bamentioning
confidence: 99%
“…The latter is reinforced by the observation that lingering mutations in DNMT3A , TET2 or ASXL1 do not confer a higher rate of AML relapse. The current definition of clonal hematopoiesis of indeterminate potential (CHIP) is generally defined as more than 2% variant allele frequency (Steensma et al , ) of driver genes [see reviews (Sano et al , ; Steensma, )] – a very low threshold for WES.…”
Section: Clonal Hematopoiesis Of Healthy and Diseased Individualsmentioning
confidence: 99%